Maternal Impaired Cognition and Infant Neglect: Exploring the Independent and Combined Effects of Maternal Executive Function and Reflective Function - Mao, Fangxiang (Journal of interpersonal violence, 2023)
Infant neglect is a common type of child maltreatment. According to the Social Information Processing theory, maternal executive function (EF) and reflective function (RF) are assumed to be important contributing factors to infant neglect. However, empirical evidence about this assumption is sparse. This was a cross-sectional study. A total of 1010 eligible women participated. The Behavior Rating Inventory of Executive Function—Adult Version, Parental Reflective Function Questionnaire, and Signs of Neglect in Infants Assessment Scale (SIGN) were used to assess maternal EF, RF, and infant neglect, respectively. Random forest was used to assess the relevant importance of maternal EF and RF. K-means clustering was used to identify the profiles of maternal EF and RF. Multivariable linear regression and generalized additive models were used to examine the independent and combined effects of maternal EF and RF on infant neglect. Each dimension of EF was linearly related to infant neglect. The associations between each dimension of RF and infant neglect were nonlinear. The inflection point for each dimension of RF was indicated. Random forest showed EF was more closely related to infant neglect. EF and RF had accumulative effects on infant neglect. Three profiles were identified. Among them, those with globally impaired EF had the highest level of infant neglect compared with those who had normal cognition or only impaired RF. Maternal EF and RF had independent and combined effects on infant neglect. Interventions with maternal EF and RF as targets are promising for reducing infant neglect.